THE IMPLEMENTATION OF âTRANSFORMATIONAL LEADERSHIPâ IN DEVELOPING ACADEMIC QUALITY - Ismaya, Bambang (Universitas Pendidikan Indonesia, 2017)
Abstractâ Transformational leadership supports higher education to frame their attitudes to shift their university forward. It has four leader higher education characteristics. Of these, idealized influence is defined as leaderâs behavior and the followerâs attributions about the leader. Inspirational motivation refers to the ways by which transformational leaders motivate and inspire those around them. Individualized consideration represents the leaderâs continuing effort to treat each individual as a special person and act as a mentor; who attempts to develop their potential. Finally, intellectual stimulation represents the leaderâs higher education effort to stimulate followers to be innovative and creative to define problems and approach them in new ways. It is considered that who demonstrate these leader higher education characteristics of transformational leadership have effects on satisfaction leader University UII Yogyakarta and better performance at university. Therefore, this study purposes to discover the level of transformational leadership that higher education demonstrate at higher education during their administrative practices on daily basis. Results reveal that university demonstrate high level of characteristics of transformational leadership in terms of idealized influence, inspirational motivation, individualized consideration and intellectual stimulation behaviors.Â Keywordsâ Transformational leadership,UII Yogyakarta higher education